Average Actual Question in CUET 2022 Slot 2

The average of six numbers is x and the average of three of these is y. If the average of the remaining three is 2, then

(1) x = y + z

(2) 3x = y + z

(30) 2x = v + z

(4) x = 2y + 2z

(1) 1

(2) 2

(3) 3

(4) 4

EXPLANATION

If the average of six numbers is denoted as x and the average of three of these is y, with the average of the remaining three being 2, then the equation 2x =y+z holds true.

Leave a Reply

Your email address will not be published. Required fields are marked *

Popular Post

Weekly Newsletter

Lorem ipsum dolor sit amet consectetur adipiscing elit ut elit tellus luctus nec.